Trends of indicators characterizing the burden of type 2 diabetes on health care systems in Ukraine and some developed countries - G. P. Mykhalchyshyn (Сучасні медичні технології)
Purpose of the study. Is to compare the epidemiological trends (2000–2017) of indicators characterizing the burden of type 2 diabetes on health care systems in Ukraine and some developed countries.